Latvian Ūsiņš ‘bee-god and patron of horses’ - Blažek, Václav (Baltistica, 2012)
In the article the Latvian theonym Ūsiņš is analyzed on the basis of historical sources (Stribingius, Stender) and in perspective of folklorе texts. The functional parallelism and possibility of etymological relationship with Vedic mythic personages, the honeybee-like Auśijá- and Aśvínau, divine twins and horse-keepers, lit. “horsemen”, indicate that the theonym may represent a syncretism of both functions and names.